The Effect of Packaging and Encapsulation Temperature of Red Chili Seeds with Trichoderma sp. on Viability and Inhibition of Fusarium sp. - Ratu, Dewanggie Sasmita; Nirwanto, Hery; Mujoko, Tri (BIOEDUSCIENCE, 2025)
Background: Fusarium sp. is one of the main threats to chili cultivation, thereby reducing its economic value. Therefore, the use of biological microorganisms, such as Trichoderma sp., is an environmentally friendly alternative for controlling Fusarium sp. Application techniques for Trichoderma sp. biological agents include seed coating or encapsulation. However, ensuring the quality and effectiveness of encapsulated products during storage and distribution remains a concern. Thus, this study aims to examine the effects of packaging type and storage temperature on the viability and efficacy of Trichoderma sp. biological agents encapsulated in red chili seeds (Capsicum annuum L.) for inhibiting Fusarium sp. Methods: This study applied a completely randomized design (CRD) factorial with two factors, namely packaging material (aluminum foil and plastic) and storage temperature (5°C, 28°C, and 36°C), resulting in 7 treatments with three replications plus a control, resulting in a total of 21 experimental units. Results: Aluminum foil packaging stored at 28°C showed the highest viability of Trichoderma sp. and the most effective antagonistic activity against Fusarium sp. Conclusion: These results provide a sustainable, environmentally friendly solution for biological-agent-based seed storage.